Aequilibrium - MPEG-DASH Video Servers Load Balancing Approaches with Software-Defined Networking - Passos, Edenilson Jônatas dos; Fiorese, Adriano (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
In recent years, with popularization of video streaming service new video distribution technologies have been created. Currently, one of the most promising ones is the Moving Picture Expert Group Dynamic Adaptive Streaming over HTTP or MPEG-DASH. Even so, with the limitation of the TCP/IP network structure, the end user quality of experience (QoE) may be affected. One issue that can affect user QoE is theworkload of content distribution servers. Thus, the imbalancing of server’s workload comprising user’s attendance can lead to a content server provider non optimized choice. This work presents two load-balancing solutions between MPEG-DASH video servers based on Software-Defined Networks, using as a balancing workload metric the content servers throughput as well as the CPU load in order to provide QoE to the end user during the server’s transitioning balance.